Implementasi Program Mini-Seminar Bahasa Inggris Bidang Kesehatan Untuk Program Studi Kesehatan Masyarakat Undikma Mataram - Kamarudin Kamarudin; Haerazi Haerazi; Sugianto Sugianto; Fathurrahman Imran; Tawali Tawali (Jurnal Pengabdian UNDIKMA, 2020)
The implementation of Mini-Seminar of English language for health at social health major of UNDIKMA Mataram aims to improve students’ English language knowledge, capability in Social Health Program of Undikma, especially English for social health both theoretically and practically. This program involved the students of social health in Undikma Mataram. The presenters or the mentors of this program were the English lecturers, and the students majoring in social health who are still active as students as the participants. The program took place in Mandalika University of Education (UNDIKMA), Mataram. The program implemented the method included planning, acting, observing in which through giving the material presentation focusing on some materials such as; English for health, eight parts of speech, modal auxiliaries, mini conversation practice realizing the materials given. The result of the implemented program revealed the high enthusiasm and interest to participate actively within the process of the program given start from the first till the end. The students also gained the increase improvement regarding the capability of using English language expression for social health, vocabulary items, and self-confident. The students also expected the same program may be re-conducted since they showed a high appreciation to the program given in terms of presentation, and guiding within the practice, so that they can enrich and improve their English language communication skill especially English for social health.